STRATEGI GURU DALAM MENINGKATKAN KEDISIPLINAN SHALAT BERJAMAAH SISWA SMP PONPES MUHAMMADIYAH TORAJA - Sulis, Sulistiawati; Andi Bunyamin; Muh Aidil Sudarmono R; Mustamin; Muhammad Syahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines how Islamic Religious Education (PAI) teachers at SMP Pesantren Pembangunan Muhammadiyah Tana Toraja improve students' congregational prayer discipline. Using a descriptive qualitative method, data were collected through observation, in-depth interviews with PAI teachers and students in grades VII-IX, and analysis of school religious activity documents. The research findings identified several effective strategies. First, a consistent persuasive approach in providing advice, emphasizing the importance of congregational prayer as a main pillar of Islam and building students' spiritual awareness. Advice is delivered wisely, considering the age and understanding of students. Second, the routine integration of religious activities, such as tadarus Al-Qur'an and congregational prayer, into the school schedule. This creates an environment that supports and encourages active participation in congregational prayer. Third, the role model of PAI teachers in carrying out worship, including congregational prayer, is a key factor in shaping student behavior. This role model has a significant positive influence. Fourth, structured supervision, through recording attendance and direct monitoring, is not only for sanctions, but as a corrective and coaching effort. An educative and dialogical approach is applied, so that students feel appreciated and guided. In conclusion, the combination of strategies has proven effective in improving students' congregational prayer discipline, as seen from the increase in their motivation, behavior, and spiritual awareness. This study recommends the implementation of this strategy in other schools as a best practice.